Recent ostracods (Crustacea: Ostracoda) of Alpine springs and adjacent springbrooks of the Southern Limestone Alps, Slovenia - Nataša Mori (Natura Sloveniae)
The ecology and distribution of ostracods in Alpine springs and springbrooks from Slovenia is presented. Benthos sampling was performed and major environmental characteristics (discharge, substrate composition, temperature, dissolved oxygen, conductivity, pH, alkalinity, sulphate, nitrate, calcium, magnesium) were measured in 12 springs and adjacent springbrooks. Sampling campaign was carried out on six sampling occasions (spring, summer, autumn in 2009 and 2010). Fourteen ostracod species were found among other fauna. The commonest and most abundant species were Psychrodromus fontinalis (Wolf, 1920) and Cavernocypris subterranea (Wolf, 1920), while the other species occurred at one or two sites at the most. Substrate composition and water temperature were statistically significant variables in explaining ostracod assemblages composition in this study.